1993
DOI: 10.1128/mcb.13.5.2882
|View full text |Cite
|
Sign up to set email alerts
|

Primer-DNA formation during simian virus 40 DNA replication in vitro.

Abstract: Studies of simian virus 40 (SV40) DNA replication in vitro have identified a small (-30-nucleotide) RNA-DNA hybrid species termed primer-DNA. Initial experiments indicated that T antigen and the polymerase a-primase complex are required to form primer-DNA. Proliferating cell nuclear antigen, and presumably proliferating cell nuclear antigen-dependent polymerases, is not needed to form this species.Herein, we present an investigation of the stages at which primer-DNA functions during SV40 DNA replication in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 28 publications
2
35
0
Order By: Relevance
“…7, A and B, lanes 13-15). Collectively, these results indicate that Rad27(367-382) stimu- 8 and 14 -16) and GST-Rad27 (lanes 9 -11 and 17-19) with Dna2 (0.05 fmol; lanes [5][6][7][8][9][10][11][12] or Dna2⌬405N (0.05 fmol; lanes [13][14][15][16][17][18][19][20]. B, overexpression of Rad27 mutant proteins under control of the ADH1 promoter in the dna2⌬405N strain suppressed the ts growth defects.…”
Section: Rad27(367-382) Peptide Stimulates Both Dna2 and Rad27 And Mumentioning
confidence: 91%
See 1 more Smart Citation
“…7, A and B, lanes 13-15). Collectively, these results indicate that Rad27(367-382) stimu- 8 and 14 -16) and GST-Rad27 (lanes 9 -11 and 17-19) with Dna2 (0.05 fmol; lanes [5][6][7][8][9][10][11][12] or Dna2⌬405N (0.05 fmol; lanes [13][14][15][16][17][18][19][20]. B, overexpression of Rad27 mutant proteins under control of the ADH1 promoter in the dna2⌬405N strain suppressed the ts growth defects.…”
Section: Rad27(367-382) Peptide Stimulates Both Dna2 and Rad27 And Mumentioning
confidence: 91%
“…In DNA replication, lagging strand DNA synthesis is more complex than leading strand because it requires discontinuous DNA synthesis and joining of short pieces of DNA called Okazaki fragments (8,9). In brief, polymerase (pol) 2 ␣-primase synthesizes an initial RNA-DNA primer on the lagging strand template that is extended by pol ␦ to generate a new Okazaki fragment.…”
mentioning
confidence: 99%
“…Pulse Labeling for Early DNA Product-The assay is essentially based on previous reports (52,53). Reaction mixtures (50 l) contained 7 mM MgCl 2 , 0.5 mM DTT, 4 mM ATP, 40 mM creatine phosphate, 30 mM HEPES (pH 7.8), 0.2 units of creatine kinase, 0.6 g of supercoiled SV40 origin-containing plasmid (pSV010), 0.84 g of T Ag, 1.4 g of recombinant RPA preparations as indicated, and RPA-depleted 293 cell lysate.…”
Section: Methodsmentioning
confidence: 99%
“…1A are synthesized during the elongation phase of a 60-min reaction. If DNA synthesis is initiated (but the products are not significantly elongated) one expects to detect the initial Okazaki fragments in a short pulse-labeled SV40 DNA replication reaction (53).…”
Section: Conserved Zinc Finger Motif In Largest Subunit Of Human Rpamentioning
confidence: 99%
“…It was previously demonstrated that the Pol ␣-primase complex initiates DNA replication by synthesizing a small RNA/DNA hybrid that has been termed primer-RNA/DNA (16,(56)(57)(58). Primer-RNA/DNA is formed exclusively from lagging-strand DNA templates, initially in the vicinity of the SV40 origin and, at later stages of synthesis, at progressively distal locations (13,25,50). Once synthesized, primer-RNA/DNA molecules are extended by a second PCNA-dependent polymerase to form full-length Okazaki fragments (16,(56)(57)(58)78).…”
mentioning
confidence: 99%